Radiographically Occult Carcinomatous Spread of Breast Cancer to the Liver: A Challenging Case - Trish Millard; Akriti Gupta; Christiana Brenin; Paul Marshall; Patrick Dillon (Case Reports in Oncological Medicine)
Metastatic carcinomatosis to the liver is a pattern of malignant infiltration that tends to provoke hepatic fibrosis. It is a rare complication of multiple solid tumor types and often seen in the absence of discrete tumor mass in the liver. We report a case of a 69-year-old woman with metastatic ductal carcinoma of the breast who presented with rising serum tumor markers and mildly cirrhotic contour of the liver on a CT scan. An early diagnosis of occult spread to the liver was made by means of a percutaneous liver biopsy showing desmoplastic response to invasive breast cancer cells found diffusely in the liver. This case highlights a rare pattern of metastatic spread of breast cancer as well as predisposing and prognostic features.